Postsynthetic bromination of UiO-66 analogues: altering linker flexibility and mechanical compliance. Issue 10 (19th November 2015) - Marshall, Ross J.; Richards, Tom; Hobday, Claire L.; Murphie, Colin F.; Wilson, Claire; Moggach, Stephen A.; Bennett, Thomas D.; Forgan, Ross S.
Abstract : Single-crystal to single-crystal post synthetic bromination of unsaturated carbon–carbon bonds in two related zirconium metal–organic frameworks leads to structures with lower elastic moduli. Abstract : A new member of the UiO-66 series of zirconium metal–organic frameworks (MOFs) is reported, and the postsynthetic bromination of its integral alkene moeities in a single-crystal to single-crystal manner is fully characterised. Nanoindentation is used to probe the bromination of unsaturated carbon–carbon bonds, in it and an analogous Zr MOF, which leads to more compliant materials with lower elastic moduli.